E.T.A. Hoffmann in Warsaw. The New Book by Peter Lachmann - Ćwiklak, Kornelia (Porównania, 2023)
Article by Kornelia Ćwiklak entitled E.T.A. Hoffman in Warsaw. The new book by Peter (Piotr) Lachmann contains an overview of the book by the Polish-German poet, writer and translator devoted to the stay of E.T.A. Hoffmann in Warsaw. The author outlined a broad historical, topographical and cultural context – especially literary and musical – of the Warsaw period of the life of the outstanding German Romantic (1804-1807). He combines a critical review of the existing state of research with an essayistic style, not free from autobiographical narration related to his own experience of Warsaw, which has been the place of the writer's life for 30 years. Translating the reviewed book into Polish would help fill the gap in knowledge about the Warsaw years of E.T.A. Hoffmann.